Modelling and simulation of flexible production line for coil winding assembly - Hazimah, Abdul Rahim (2015)
This thesis deals with modelling and simulation of flexible production line for coil winding assembly. Flexible production line is a production line capable to change any changes in different product simultaneously and continuously. The reason need of developing flexible production line is to have a high productivity, good quality and low cost and to ensure smoothness of the production line. The main problem at production line is the usage of the conveyer where it can make the space become crowded. The proposed method is by changing to cell manufacturing layout because it is way of lean manufacturing to guide company to implement less waste as possible for product variety to the customers. The objective of this project is to investigate current performance of coil winding assembly and to model and simulate flexible production line using Pro Model simulation software. In this case study, the framework of project will cover on research of cycle time, product mix, flexibility and efficient usage of space. A company has been selected is Vacuumschmelze(M) Sdn Bhd and simulation ProModel 7.0 Software Student Version was used to complete the case. The project is begin by identifying and evaluating the problem occur at the production line. The current condition of production line layout was modelled using simulation ProModel 7.0 Software Student Version. The simulation was run in 8 hours by following the working schedule at company. A total of 10 replication has been set for this project. From the result, the percentage show high utilization from the current performance. The percentage of operation is increase from 9.29% to 63.27%. From the result, it can be concluded that the changing of the new layout by changing the conveyer to the U-shape layout was the most significant factor in productivity enhancement of the production.